Pencegahan Covid-19 Pada Pemuda GBIS Kristus Pengharapan Medan - Novita Hasiani Simanjuntak (Jurnal Visi Pengabdian Kepada Masyarakat, 2021)
Covid-19 is still a pandemic, and showing an increase globally. Government policies are needed to assist youth in coping with this disaster by implementing effective measures. Thus, counseling is needed for youth to increase knowledge, know how to protect oneself, protect themselves and others in order to achieve preparedness against this disaster. This Community Service in the form of an outreach entitled "Prevention of Covid-19 on the Youth of GBIS Christ Hope Medan" was carried out online through the zoom cloud meetings application. Participants of the counseling were 23 GBIS Christ Hope Medan Youths. The technical implementation of this community service consists of opening by the MC, counseling, video playback, presenting posters, demonstrating how to wash hands and wearing masks, as well as a QA session, and finally participants filling out feedback via google form. Participants were very enthusiastic and interested in this extension, this can be seen from the feedback given by extension participants via google form. Most of the extension participants thought this counseling went very well (68.75%), and all participants agreed that this extension was very useful for them, because they got more knowledge about prevention, especially by washing hands properly, and increased endurance. The first conclusion is that the topic of counseling presented is in accordance with the needs of the extension participants, because Covid-19 is still a disease that has caused a pandemic with a high mortality rate until now. Second, it can invite young people to be able to further improve personal and environmental hygiene and a healthy lifestyle in reducing Covid-19 transmission and implement health protocols issued by the government to tackle the spread of Covid-19.